A new species of the hysius species-group of Calisto Hübner (Lepidoptera, Nymphalidae, Satyrinae) and insights into the status of different populations currently attributed to C. grannus Bates - Aguila, Rayner Nuñez; Genaro, Julio A.; Peréz-Asso, Antonio R.; Hausmann, Axel (Zootaxa, 2017)
A species belonging to the hysius group of Calisto is newly described. Calisto bahoruco new species inhabits the easternmost area of the southern Hispaniola Sierra de Bahoruco. The species is closely related to C. hysius Godart, another endemic from the southern mountains. The two species differ in average forewing length (larger in C. hysius), the relative size of ocelli (larger in C. bahoruco), and in the darker ground color with more contrasted paler edges of lines at underside of wings in C. bahoruco compared to C. hysius. Their male genitalia differ in the shape of the uncus and in the heavier sclerotization in C. bahoruco. COI barcodes bear a minimum of 15 differences between the two species. All species delimitation methods applied to the COI dataset, ABGD, BIN, bPTP, mPTP, and PTP yielded 8 species. The exception was the GMYC that failed to recognize the new taxon and oversplitted several other taxa. COI gene tree obtained by Maximum Likelihood and Bayesian have identical topologies agreeing with a multilocus phylogeny reconstructed in a previous work on Calisto and placing the new taxon as sister of C. hysius. Additionally, we provide new evidence of the conspecific nature of all named populations within Calisto grannus group.